2011
DOI: 10.1071/ah10951
|View full text |Cite
|
Sign up to set email alerts
|

A cost analysis of febrile neutropenia management in Australia: ambulatory v. in-hospital treatment

Abstract: This study outlines a cost structure for a safe and comprehensive ambulatory care program comprised of an early discharge pathway with outpatient follow-up, and promotes this as a cost effective approach to managing 'low-risk' febrile neutropenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…An Australian cost analysis showed a 30% saving for ambulatory care strategies when compared with standard hospital care [49]. Considering the high economic cost for the health care system of hospitalized BC patients with FN, managing as many patients as possible in an outpatient setting should be a key task in modern medical oncology.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian cost analysis showed a 30% saving for ambulatory care strategies when compared with standard hospital care [49]. Considering the high economic cost for the health care system of hospitalized BC patients with FN, managing as many patients as possible in an outpatient setting should be a key task in modern medical oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Additional intangible yet important costs include parental and patient anxiety, travel costs, and missed time from school or work. In the oncology realm, research has identified effective cost savings when stratifying low‐risk patients with fever and neutropenia for conservative management, and the population of patients with AIN presents an optimal group for consideration of such conservative management …”
Section: Discussionmentioning
confidence: 99%
“…This translates to 15 patients per year, or 1 patient per 3 weeks. It has been suggested that more than two patients per week must be managed with this strategy in order for the development and maintenance of necessary infrastructure to be cost effective . Therefore, outpatient management of NF patients may not be practical at present at our regional cancer centre.…”
Section: Discussionmentioning
confidence: 99%